Approximating Fixed Points via Hybrid Enriched Contractions in Convex Metric Space with an Application - Bhumika Rani; Jatinderdeep Kaur; Satvinder Singh Bhatia (Axioms)
In the present study, we define hybrid enriched contractions of the Hardy–Rogers type and of the Ćirić–Reich–Rus type in the framework of convex metric space. We demonstrate the presence and the approximation of fixed points for contraction mappings by using Krasnoselskij iteration. The main conclusions of this study are shown to be corollaries or implications of multiple important fixed point theory findings. Some examples have also been provided to show the validity of our results. Towards the end of this paper, we study the solution of the nonlinear equations as an application of our main results.